Molecular characterisation of antibiotic resistant genes and development of real time loop- mediated isothermal amplification for rapid detection of virulence gene (speB) in group a streptococci - Onyema, Azi Simon (2020)
Group A streptococcus is one of the major human pathogens responsible for over 600 million infections annually. This “flesh-eating bug” has caused more than 600,000 deaths per annum globally. Heightened concerns have been escalating among the scientists and physicians due to its ability to cause serious invasive disease and long-term sequelae. Loop mediated isothermal amplification (LAMP) has been considered as a novel approach for its cost - effectiveness, good reliability, high sensitivity results, and can be performed in a rural setting with less sophisticated equipment. Thus, this study is aimed to develop a rapid, reliable and cost -effective diagnostic approach for the detection of streptococcal pyrogenic exotoxin B (speB) from GAS isolates by RT-LAMP technique. Forty-three GAS isolates were obtained from stock culture with 31 (72.1%) and 12 (27.9%) isolates from non-invasive and invasive samples respectively. Re-identification of these isolates was carried out using several conventional methods and confirmed with 16s rRNA. Antimicrobial susceptibility testing was performed using Kirby-Bauer disk diffusion method and interpreted according to CLSI guidelines. Preliminary screening for antibiotic resistance genes (tetM, lnuA, ermA, ermB, mefA) and virulence genes, (speB, and prtF1) were performed using PCR amplification to choose variables for real time-LAMP development. Some categorical variables were tested by Chi-square analysis and p values less than 0.05 were considered significant. All GAS isolates (100%) were sensitive to erythromycin and azithromycin. Twenty-five (58.1%) and 7 (16.3%) of them exhibited resistance to doxycycline and clindamycin respectively. There were no inducible MLSB (iMLSB) or constitute MLSB (cMLSB) or MS phenotypes detected among GAS isolates but an L-phenotype 7 (16.3%) was observed. Regarding virulence genes, 43 (100 %) and 20 (46.5%) of GAS isolates carried speB and prtF1 genes, respectively. In addition, tetM and lnuA genes were detected in all doxycycline and clindamycin-resistant isolates (100% for each). speB, the major cause of pathogenicity in GAS that was detected up to 100% in the preliminary gene, was used as a marker to progress with the development of real -time loop mediated isothermal amplification (RT-LAMP). ATCC 19616, (S. pyogenes, positive control) and no DNA template as negative control) were used after optimization of primers, time and RT- LAMP reagents for the initial development. The optimal RT- LAMP condition was obtained at 63◦C for 45 min using laboratory heating block and Real-time turbidimeter machine (LA- 500 Eiken Company, Japan) respectively. Forty- three clinical isolates of S. pyogenes as described earlier were also used to verify the possibility of the RT-LAMP assay in the detection speB gene followed by nine bacteria strains including Streptococcus pyogenes and other non- GAS bacteria strains (from American Type Culture Collection) and clinical isolates in evaluating the specificity and sensitivity following serial dilutions of 10- 2 to 10-6ng/μl. The detection limit of our RT-LAMP was 0.001ng/μl of the template, showing higher sensitivity than conventional LAMP and PCR detection limit of 0 .000001 ng/μl and 0.001 ng/μL making it 100,000- folds more sensitive than PCR and 100-fold more sensitive than conventional LAMP assay. The detection rate of speB using RT-LAMP 100% while PCR was 93% with conventional PCR primer set. In conclusion, the improved rapidity for detection of the speB which contribute greater percentages in GAS virulence among other factors by the RT-LAMP technique with its specificity and sensitivity using less sophisticated equipment, simple to perform and cost-effective, is expected to be a new frontier in the reliable method for the diagnosis of S. pyogenes infection and will soon replace other time- consuming and costly molecular assays. The technique particularly is suitable for rural or community hospitals in developing nations with middle income level.